Henry L. Dawes papers - Dawes, Henry L. (Henry Laurens), 1816-1903.; Dawes, Anna Laurens, 1851-1938.; Dawes, Electa Allen Sanderson, 1822-1901.
Correspondence, memoranda, letterbooks, diaries, speeches, reports, notebooks, biographical material, family papers, clippings, printed matter, scrapbooks, photographs, and other papers primarily concerning Dawes's service as U.S. senator and representative, member of the Senate Committee on Indian Affairs, and chairman of the U.S. Commission to the Five Civilized Tribes. Includes material pertaining to American Indian affairs; congressman Oakes Ames; the George Chorpenning claim case; civil service; Gallaudet College, Washington, D.C.; political campaigns and conventions; the railroad construction company Credit Mobilier of America; Reconstruction; tariff; and the U.S. Weather Bureau. Family papers includes diaries and correspondence of Dawes; his wife, Electa Allen Sanderson Dawes; and daughter, Anna Laurens Dawes. Also includes an incomplete biography of Henry L. Dawes by Anna Laurens Dawes.
Correspondents include Lyman Abbott, Charles Allen, Oakes Ames, James Gillespie Blaine, Montgomery Blair, Cornelius Newton Bliss, Samuel Bowles, Selwyn Zadock Bowman, Calvin Clifford Chaffee, William Claflin, Schuyler Colfax, Cushman Kellogg Davis, Edward Everett, Cyrus W. Field, James A. Garfield, Edward Everett Hale, Sr., Joseph R. Hawley, George Frisbie Hoar, Mark Hopkins, Henry Oscar Houghton, L.Q.C. Lamar, Robert Todd Lincoln, Henry Cabot Lodge, John Davis Long, George Brinton McClellan, S.S. McClure, Nelson Appleton Miles, John Tyler Morgan, T.J. Morgan, Justin S. Morrill, John W. Noble, Orville Hitchcock Platt, William P. Porter, Theodore Roosevelt, Philip Henry Sheridan, John C. Spooner, Charles Sumner, Ida M. Tarbell, Lyman C. Thayer, Edward R. Tinker, E.B. Washburne, and Herbert Welsh.
The autograph correspondence collection includes letters to Henry L. Dawes and Anna Laurens Dawes from Charles Francis Adams, Henry Adams, Susan B. Anthony, George Ashmun, Alexander Graham Bell, Maude Ballington Booth, Benjamin F. Butler, Frances Folsom Cleveland, Richard Henry Dana, Grace H. Dodge, Theodore F. Dwight, Samuel A. Eliot, Alice C. Fletcher, John Watson Foster, Richard Watson Gilder, Sir Ben Greet, Edward Everett Hale, Sr., George Frisbie Hoar, O.O. Howard, Julia Ward Howe, F.D. Huntington, Sarah Orne Jewett, Frank O. Lowden, S.S. McClure, Simon Newcomb, Alice Freeman Palmer, Gifford Pinchot, Ella Farman Pratt, Vinnie Ream, Alice Robertson, Eliza Ruhamah Scidmore, William H. Taft, Booker T. Washington, Robert C. Winthrop, and Mary Emma Woolley.
U.S. representative and senator from Massachusetts.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Abbott, Lyman, -- 1835-1922 -- Correspondence; Adams, Charles Francis, -- 1807-1886 -- Correspondence; Adams, Henry, -- 1838-1918 -- Correspondence; Allen, Charles, -- 1827-1913 -- Correspondence; Ames, Oakes, -- 1804-1873.; Ames, Oakes, -- 1804-1873 -- Correspondence; Anthony, Susan B. -- 1820-1906 -- Correspondence; Ashmun, George, -- 1804-1870 -- Correspondence; Bell, Alexander Graham, -- 1847-1922 -- Correspondence; Blaine, James Gillespie, -- 1830-1893 -- Correspondence; Blair, Montgomery, -- 1813-1883 -- Correspondence; Bliss, Cornelius Newton, -- 1833-1911 -- Correspondence; Booth, Maud Ballington, -- 1865-1948 -- Correspondence; Bowles, Samuel, -- 1826-1878 -- Correspondence; Bowman, Selwyn Zadock, -- 1840-1928 -- Correspondence; Butler, Benjamin F. -- 1795-1858 -- Correspondence; Chaffee, Calvin Clifford, -- 1811-1896 -- Correspondence; Chorpenning, George, -- 1820-1894 -- Claims vs. United States; Claflin, William, -- 1818-1905 -- Correspondence; Cleveland, Frances Folsom, -- 1864-1947 -- Correspondence; Colfax, Schuyler, -- 1823-1885 -- Correspondence; Dana, Richard Henry, -- 1815-1882 -- Correspondence; Davis, Cushman Kellogg, -- 1838-1900 -- Correspondence; Dodge, Grace H. -- 1856-1914 -- Correspondence; Dwight, Theodore F. -- Correspondence; Eliot, Samuel A. -- 1862-1950 -- Correspondence; Everett, Edward, -- 1794-1865 -- Correspondence; Field, Cyrus W. -- 1819-1892 -- Correspondence; Fletcher, Alice C. -- 1838-1923 -- Correspondence; Foster, John Watson, -- 1836-1917 -- Correspondence; Gilder, Richard Watson, -- 1844-1909 -- Correspondence; Garfield, James A. -- 1831-1881 -- Correspondence; Greet, Ben, -- Sir, -- 1857-1936 -- Autographs; Hale, Edward Everett, -- Sr., -- 1822-1909 -- Correspondence; Hawley, Joseph R. -- 1826-1905 -- Correspondence; Hoar, George Frisbie, -- 1826-1904 -- Correspondence; Hopkins, Mark, -- 1802-1887 -- Correspondence; Houghton, Henry Oscar, -- 1823-1895 -- Correspondence; Howard, O. O. -- 1830-1909 -- Correspondence; Howe, Julia Ward, -- 1819-1910 -- Correspondence; Huntington, F. D. -- 1819-1904 -- Correspondence; Jewett, Sarah Orne, -- 1849-1909 -- Correspondence; Lamar, L. Q. C. -- 1825-1893 -- Correspondence; Lincoln, Robert Todd, -- 1843-1926 -- Correspondence; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; Long, John Davis, -- 1838-1915 -- Correspondence; Lowden, Frank O. -- 1861-1943 -- Correspondence; McClellan, George Brinton, -- 1826-1885 -- Correspondence; McClure, S. S. -- 1857-1949 -- Correspondence; Miles, Nelson Appleton, -- 1839-1925 -- Correspondence; Morgan, John Tyler, -- 1824-1907 -- Correspondence; Morgan, T. J. -- 1839-1902 -- Correspondence; Morrill, Justin S. -- 1810-1898 -- Correspondence; Newcomb, Simon, -- 1835-1909 -- Correspondence; Noble, John W. -- 1831-1912 -- Correspondence; Palmer, Alice Freeman, -- 1855-1902 -- Correspondence; Pinchot, Gifford, -- 1865-1946 -- Correspondence; Platt, Orville Hitchcock, -- 1827-1905 -- Correspondence; Porter, William P. -- 1819-1873 -- Correspondence; Pratt, Ella Farman, -- 1837-1907 -- Correspondence